2021
DOI: 10.1103/physrevfluids.6.044001
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of a shock-accelerated heavy cylindrical bubble under nonequilibrium conditions of diatomic and polyatomic gases

Abstract: Behavior of a shock-accelerated heavy cylindrical bubble under nonequilibrium conditions of diatomic and polyatomic gases Singh, Satyvir; Battiato, Marco 2021 Singh, S. & Battiato, M. (2021). Behavior of a shock-accelerated heavy cylindrical bubble under nonequilibrium conditions of diatomic and polyatomic gases. Physical Review Fluids, 6(4), 044001-.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…A detailed validation study of the present numerical scheme for shock wave interaction with cylindrical and square bubbles was presented by Singh and coauthors [30,31,37], where good agreement was obtained for shock wave structures, positions, and bubble deformations. In the current study, the numerical results are validated with the experimental study of Zhai et al [32] for checking the validity of the present computational model and the in-house developed explicit modal DG code.…”
Section: Validation Of the Numerical Solvermentioning
confidence: 76%
See 1 more Smart Citation
“…A detailed validation study of the present numerical scheme for shock wave interaction with cylindrical and square bubbles was presented by Singh and coauthors [30,31,37], where good agreement was obtained for shock wave structures, positions, and bubble deformations. In the current study, the numerical results are validated with the experimental study of Zhai et al [32] for checking the validity of the present computational model and the in-house developed explicit modal DG code.…”
Section: Validation Of the Numerical Solvermentioning
confidence: 76%
“…At high Mach numbers (M s = 2.5-3.0), Rybakin and Goryachev [29] studied numerically the deformation and instability of a low-density gas bubble, the formation and evolution of vortex rings, and the shock wave-bubble configuration. Recently, Singh and Battiato [30] analyzed numerically the behavior of a shock-accelerated cylindrical heavy bubble at low Mach number (M s = 1.21) under the nonequilibrium conditions of diatomic and polyatomic gases. Further, this research work was extended by Singh et al [31] to investigate the impact of bulk viscosity on the flow morphology of a shock-accelerated cylindrical light bubble.…”
Section: Introductionmentioning
confidence: 99%
“…While Stokes' hypothesis is believed to be valid in the case of monatomic gases such as argon, there is growing proof that this is not the case with diatomic and polyatomic gases such as nitrogen, methane, and carbon dioxide. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Examples of such cases include the inner structure of strong shock waves in diatomic gases and hypersonic entry into the Mars atmosphere, which consists mostly of carbon dioxide. A recent experimental study on the second-mode instability in the laminar-toturbulence transition in hypersonic boundary layers 40 showed that, for a real diatomic gas, the growth and decay of the second mode are accompanied by a dilatation process that leads to a 50% increase in dilatation dissipation in comparison with Stokes' hypothesis.…”
Section: Articlementioning
confidence: 99%
“…Later, Singh et al 48 investigated the topology of the high-order constitutive model beyond the conventional NSF equations and Stokes' hypothesis. Recently, Singh and Battiato 49 numerically studied the behavior of a shock-accelerated cylindrical heavy bubble under the nonequilibrium conditions of diatomic and polyatomic gases.…”
Section: Articlementioning
confidence: 99%
“…Besides these experiential works, numerous advanced numerical approaches have been developed to enhance our understanding of the complex interactions between shocks and cylindrical/spherical bubbles. These methodologies include contributions from researchers such as Quirk and Karni [28], Giordano and Burtschell [29], Bagabir and Drikakis [30], Niederhaus et al [31], and Wang et al [32], and more recent works by Singh et al [33,34]. Additionally, specific investigations have concentrated on shocked elliptical gas bubbles, with a primary focus on exploring how the aspect ratio impacts flow dynamics, particularly regarding bubble deformation and the mixing of fluids [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%